A 3‐D hand gesture signature based biometric authentication system for smartphones. Issue 11 (23rd February 2016) - Sun, Ziwen; Wang, Yao; Qu, Gang; Zhou, Zhiping
Abstract: The authentication mechanism being equipped in most of the smartphones, by detecting a 4‐digit password or a simple pattern, are easy to be hacked and impersonated. In this paper, a 3‐D hand gesture signature (HGS) based biometric authentication system is designed and implemented by taking advantage of the on‐phone accelerometer to capture the 3‐D acceleration information when user makes a gesture to gain access to the phone. The captured data will be processed through a sequence of signal processing such as data smooth, gesture spotting, sequence alignment, and interpolation, and then a match rule will be used to compare the processed data and the genuine user's registered pattern to determine whether granting the access to the phone to the user. And an automatic template updating strategy based on cluster analysis is proposed to improve the stability of the system. The 3‐D HGS authentication system has been implemented on real smartphones, and the results tested for a total of 76 520 times by 19 users show very low false acceptance (0.27%) and false rejection rates (4.65%). Furthermore, comparison tests have been carried out among the 3‐D HGS and two similar authentication systems by exporting the real gesture samples from the phones to a desktop PC, the simulation results reveal the 3‐D HGS system has the best authentication accuracy. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, a three‐dimensional (3D) hand gesture signature‐based biometric authentication system is designed and implemented by taking advantage of the on‐phone accelerometer to capture the 3D acceleration information when user makes a gesture to gain access to the phone. The captured data will be processed through a sequence of signal processing such as data smoothing, gesture spotting, sequence alignment, and interpolation, and then a match rule will be used to compare the processed data and the genuine user's registered pattern to determine whether to grant user access to the phone. And an automatic template updating strategy based on cluster analysis is proposed to improve the stability of the system. The comparison tests show that the proposed methods outperform two similar authentication systems. Furthermore, the 3D hand gesture signature authentication system has been implemented on real smartphones with low false acceptance.